the Local Wisdom Of Corn In Maintaining Food Security - Sinthia Watremny; Leunard O. Kakisina; Risyart A. Far far (International Journal of Economics, Business and Innovation Research, 2023)
This research was conducted to find out what local wisdom exists in Nusiata Village in maintaining food security and the values of local wisdom in Nusiata Village. The sample taken in this study was 20 respondents using the simple random sampling method. The analysis method used in this study uses qualitative analysis obtained from primary data and secondary data. The results of this study explain the local wisdom that occurs in Nusiata Village in maintaining food welfare through the consumption of corn (Zea mays) as the staple food of the people of Nusiata Village, this habit is carried out for generations as the staple food of the people of Nusiata Village. This tradition of consuming corn is proven to make the people of Nusiata Village independent and not dependent on rice which is the staple food of the Indonesian people. The values in maintaining food security in Nusiata Village are that the community still maintains traditions such as helping each other (narera) in clearing land, continuing to plant corn and consuming corn as a staple food.